Psycholinguistic experiment as a way of diagnosing cultural and speech competence schoolchildren (Филологический класс, 2013)
The paper covers the results of the use of psycholinguistic experiment (methodology to determine the correctness of the statement) is applicable to the analysis of speech errors. Using this method, according to the author, allows you to diagnose the level of the language competence of the students, and to identify some directions of work on the prevention of speech violations in written works of schoolchildren.